Papers, 1804 thru 1870 - Trimble, Allen, 1783-1870 (Early Ohio political leaders project., 1977)
State legislator and Governor of Ohio. Personal and business correspondence, relating to family matters, mercantile trade, War of 1812, Ohio militia, and canals; gubernatorial administrative and constituent correspondence, including job requests, petitions, and pardons; and newspaper clippings from Hamilton, Highland, and Ross Counties, Ohio, relating to Trimble's role in the American Party.